Ultrasonographic analysis of the anatomical relationship between femoral vessels in the upper part of thigh in critically ill patients– a cross sectional study - Suresh Kumar V.K.; Deepak Vijayan; Shamim Kunhu; Boban Varghese (International Journal of Medical Research and Review, 2018)
Objective: Femoral vessels are one of the frequently used sites of cannulation in intensive care units. In resource limited settings cannulations are done blindly without ultrasonographic guidance based on a traditional belief that in the upper thigh vein keeps a medial relationship to artery. In this trial we tried to analyse the anatomical relationship of femoral vein to femoral artery using ultrasound in critically ill patients.Methods: This cross sectional study analysed the anatomical relationship of femoral vein to femoral artery at 2cm, 4 cm and 6 cm from the mid inguinal point in both thighs of the patients using ultrasonography. The study was done among patients admitted in a multidisciplinary intensive care unit.Results: Three hundred limbs of one hundred and fifty patients were analysed by ultrasonography. A total of 900 measurements were taken at three different levels of both legs. At 2 cm below the mid inguinal point, in 256 limbs (85.3%) femoral vein was medial to femoral artery (95% Confidence Interval82.82% to 89.14%), at 4 cm below the mid inguinal point, in 210 limbs (70%) femoral vein was postero medial to femoral artery (95% CI64.47% to 75.13%),and at6 cm below the mid inguinal point in 200 limbs(66.7%)femoral vein was posterior to femoral artery(95% CI 61.02% to 71.98%).Conclusion: Femoral vein showed variable relationship to femoral artery in the upper part of the thigh. As the distance increased from mid inguinal point, variation from normal relationship was also found to be increasing.